ANALISIS PERAN AKUNTANSI FORENSIK DALAM PENGKUNGKAPAN TINDAK PIDANA KORUPSI - Cahya, Angela Restu; Espa, Vitriyan; Fahmi, Muhammad (Worksheet : Jurnal Akuntansi, 2025)
This study aims to examine the role of forensic accounting in disclosing corruption cases in Indonesia, identify the methods applied in forensic accounting practices, and explore challenges encountered in its implementation. A qualitative approach is used with a library research method to gain in-depth insights into the application of forensic accounting in combating corruption. The data utilized are secondary data collected from academic journals, books, research reports, legal documents, and other sources. The findings reveal that forensic accounting plays vital role in the investigation of corruption through fraud detection, financial reconstruction, evidence identification and collection, and support during legal proceedings. Techniques applied include data analysis, forensic auditing, digital forensic analysis, interviews, the use of big data and artificial intelligence, and whistleblowing systems. Although the implementation of forensic accounting in Indonesia has shown progress, it still faces obstacles such as limited human resources, high investigative costs, complex cases, and restricted access to data. To address these challenges, the study suggests strategic improvements through detective, repressive, and preventive approaches, capacity building, and technological advancement. Optimizing forensic accounting practices contributes not only to uncovering corruption cases but also to strengthening internal control, preventing fraud, and restoring public trust in governance.